BADAN USAHA MILIK GEREJA: STRATEGI PARTISIPATIF MENUJU KEMANDIRIAN EKONOMI JEMAAT DI PEDESAAN - Mosooli, Ermin Alperiana; Lembolangi, Lefran; Fredy Sosinggih; Yuliana Paluet; Epin Tangaan (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2025)
This study addresses the financial and institutional limitations faced by rural local churches in establishing Church-Owned Enterprises (Badan Usaha Milik Gereja/BUMG), with a specific focus on the Oikumene Indangsari Congregation in Banggai Regency, Central Sulawesi Province. Although the congregation does not yet operate a formal business entity, it is supported by an economically active community of entrepreneurs, indicating significant potential to support church-led economic initiatives. Employing a mixed-methods approach with an exploratory descriptive design, the research utilizes interviews, focus group discussions (FGDs), and a Guttman scale questionnaire. The findings reveal that the congregation's entrepreneurs possess strong spiritual and social commitment, substantial entrepreneurial experience, and active roles in the church’s organizational structure. Nevertheless, limitations in managerial capacity and business formalization remain challenges. The study concludes that the active participation of congregation members serves as a strategic asset for developing a BUMG, especially when supported by targeted training, mentoring, and a professional institutional framework. The BUMG holds promise as a collective platform that integrates faith-based values with economic practices, fostering both the sustainability of ministry and the financial autonomy of the local church.